Wrap‐Around Core–Shell Heterostructures of Layered Crystals. Issue 29 (3rd June 2019) - Sutter, Peter; Wang, Jia; Sutter, Eli
Abstract: Engineered heterostructures create new functionality by integrating dissimilar materials. Combining different 2D crystals naturally produces two distinct classes of heterostructures, vertical van der Waals (vdW) stacks or 2D sheets bonded laterally by covalent line interfaces. When joining thicker layered crystals, the arising structural and topological conflicts can result in more complex geometries. Phase separation during one‐pot synthesis of layered tin chalcogenides spontaneously creates core–shell structures in which large orthorhombic SnS crystals are enclosed in a wrap‐around shell of trigonal SnS2, forcing the coexistence of parallel vdW layering along with unconventional, orthogonally layered core–shell interfaces. Measurements of the optoelectronic properties establish anisotropic carrier separation near type II core–shell interfaces and extended long‐wavelength light harvesting via spatially indirect interfacial absorption, making multifunctional layered core–shell structures attractive for energy‐conversion applications. Abstract : Core–shell structures of monocrystalline layered cores wrapped in few‐layer shells are realized via one‐pot synthesis and spontaneous phase separation of van der Waals crystals. Abundant interfaces with different core and shell layer orientations create unique optoelectronic properties, notably anisotropic charge transfers and spatially indirect interfacial absorption, promising efficient light harvesting to photon energies significantly below the bandgaps of the constituent semiconductors.